Cemented single crown retention on dental implants: an in vitro study - Rues, Stefan; Fugina, Melissa; Rammelsberg, Peter; Kappel, Stefanie (The international journal of prosthodontics, 2017)
Purpose: The aim of this study was to determine the influence of selected cements, abutment heights, and aging on the retention of zirconia crowns on zirconia abutments. Materials and Methods: Zirconia crowns and abutments (height: 4.0 or 5.5 mm) were sandblasted and retained using five different cements. Axial pull-off tests were performed after thermocycling or 3 days of water storage. Results: An increase in abutment height was associated with an increase in decementation force when permanent cementation was tested. The aging protocol showed that temporarily cemented crowns showed a significant retention decrease, while use of a permanent cement led to a moderate increase. Conclusion: Only use of permanent cements ensures clinically adequate decementation forces.